UJI EFEKTIFITAS PERASAN KUNYIT PUTIH (Curcuma spp.) TERHADAP PERTUMBUHAN Escherechia coli - Evy Ratnasari Ekawati (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2016)
This study aims to determine effectiveness of the juice of white turmeric (Curcuma spp.) to the growth ofEscherechia coli. This study was an experimental study using disc diffusion method to look at theeffectiveness of the juice of white turmeric (Curcuma spp.) to the growth of Escherechia coli. The juice ofwhite turmeric used has concentration of 20%, 40%, 60%, 80% and 100%. The results showed the juice ofwhite turmeric (Curcuma spp.) at concentration of 40% to 100% has the potential to inhibit the growthEscherechia coli. Nonetheless, based on the statistical test concentration of 40% and 60% was notsignificantly different from the control and concentration of 20%. Concentration of 80% and 100%significantly different from the control and concentration of 20%, 40%, 60%. Concentration of 80% wassignificantly different from 100% concentration, the more effective use of freshly white turmeric (Curcumaspp.) with 100% concentration to accelerate the process of growth inhibition Escherechia coli. Keywords: the juice of white turmeric (Curcuma spp.), Escherechia coli